The dynamic analysis of rotors mounted on composite shafts with internal damping - De Paula Mendonca, Willy Roger [UNESP]; De Medeiros, Everton Coelho [UNESP]; Rezende Pereira, Artur Luiz [UNESP]; Mathias, Mauro Hugo [UNESP] (Elsevier B.V., 2017)
This paper presents a study on the dynamic analysis of rotors mounted on composite shafts. The dynamic analysis of these rotors differs from conventional analysis due to the existence of internal damping in the shaft. The shafts are made of composite materials, which exhibit viscoelastic behavior. The equations of motion for these rotors represent the influence of internal damping on the dynamic behavior of the rotor system. Composite materials can be manufactured using different layups. This study reviews the methodology that can be used to predict the equivalent mechanical properties of composite shafts. Several finite element simulations are presented to show the influence of the composite shaft layup on the dynamic behavior of the rotor. The simulation results are used to present the influence of the layup on Campbell diagrams, critical speeds, instability thresholds and frequency response functions. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Critical speed; Finite element; Loss factor; Viscoelastic; Damping; Classical laminate theory